Comparative Study of Terminalia catappa Linn. Leaf Extracts Against Aeromonas hydrophila - Putra, Prily Lovian; Hariati, Anik Martinah; Prihanto, Asep Awaludin (The Journal of Experimental Life Science, 2025)
Motile Aeromonas Septicemia (MAS), primarily caused by Aeromonas hydrophila, remains a critical threat in aquaculture due to its high mortality rates and economic impact. This study evaluated the antibacterial activity of crude Terminalia catappa L. leaf extract prepared using maceration and microwave-assisted extraction (MAE) methods against A. hydrophila in vitro. Phytochemical screening confirmed the presence of flavonoids, triterpenoids, tannins, and saponins in both extracts. The MIC test showed that MAE resulted in slightly lower optical density values than maceration, suggesting greater inhibition potential. Disk diffusion assays revealed that both extracts produced clear inhibition zones, with the MAE extract generating larger zones at equivalent concentrations. Scanning Electron Microscopy (SEM) confirmed morphological damage and lysis in A. hydrophila cells exposed to the extract. These findings demonstrate that T. catappa L. leaf extract exhibits significant antibacterial activity against A. hydrophila, with MAE being the more effective extraction method to enhance bioactivity.